Surgical resection for patients with recurrent or metastatic gastrointestinal stromal tumors: a protocol for a systematic review and meta-analysis update - Zhaolun Cai; Chunyu Xin; Zhiyuan Jiang; Chunyu Liu; Chaoyong Shen; Guozhen Zhao; Yuan Yin; Xiaonan Yin; Zhou Zhao; Mingchun Mu; Bo Zhang (Systematic Reviews, 2021)
Abstract Background There are limited data on the clinical benefits of adding surgical resection in patients with recurrent or metastatic gastrointestinal stromal tumors (GISTs). This protocol outlines the planned scope and methods for a systematic review and meta-analysis update that will compare the clinical outcomes of surgical resection combined with tyrosine kinase inhibitor (TKI) with TKI treatment alone in patients with recurrent or metastatic GISTs. Methods This review will update a previously published systematic review by our team. This protocol is presented in accordance with the PRISMA-P guideline. PubMed, Embase, and Cochrane Central Register of Controlled Trials will be systematically searched and supplemented by a secondary screening of the references of all included studies. We will include randomized controlled trials (RCTs) and non-randomized studies (NRS) in this review update. The outcomes evaluated will be overall survival and progression-free survival. Two reviewers will independently screen and select studies, extract data from the included studies, and assess the risk of bias of the included studies. Data extracted from RCTs and NRS will be analysed and reported separately. Preplanned subgroup analyses and sensitivity analyses are detailed within this protocol. The strength of the body of evidence will be assessed using GRADE. Discussion This systematic review and meta-analysis update will provide a current assessment of the evidence for the role of surgery in patients with recurrent or metastatic advanced GISTs. These findings will be used by the Chinese Society of Clinical Oncology (CSCO) GIST guideline recommendations on surgical treatment for recurrent or metastatic advanced GIST patients in China. Systematic review registration This protocol was prospectively registered in the Open Science Framework Registry ( https://osf.io/xus7m ).